KEPUASAN LAYANAN JASA GOFOOD OLEH GOJEK PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS TANJUNGPURA - Aprianti, Yulia Elsa; Achmadi, Achmadi; Syahrudin, Husni (Universitas Tanjungpura, 2023)
This research is to find out the Satisfaction of GoFood Services by Gojek to Economic Education Students of FKIP Tanjungpura University using a case study qualitative approach. The data sources obtained in this study consisted of 10 people with 3 groups, namely, 6 students, 2 Gojek drivers and 2 Gojek partners. The methods used in data collection are interviews and documentation. The results of research on Economics Education students show that satisfaction with Gojek services, the type of GoFood service in terms of reliability is that they often buy and use service products that are accurate and according to their needs, in terms of responsiveness there is a form of satisfaction that is in the form of a perceived fast response in the form of replies when gojek has direct contact questions via telephone or chat forums, in terms of empathy (empathy) there is a form of satisfaction in the form of caring, giving more personal attention to customers, in terms of physical evidence (tangible) there is satisfaction in the form of an assessment of physical appearance, equipment used, cleanliness and tidiness of communication media.